Implementation of E-Business Strategy to Increase Competitive Advantage (Case Study At PT. Airasia Indonesia) - Rahmadhani, Sophia; Rizki, Anggita; Siregar, Ahmad Ihsan Fiqih; Nurbaiti, Nurbaiti (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
E-business is the use of the Internet and other networks and information technology to facilitate the process of electronic commerce, business cooperation and communication, and business activities on the web. In other words, E-business has a wider scope than e-commerce AirAsia is one of the airlines that uses e-business implementation in its core business functions. Through http://www.airasia.com customers only need to visit the website from AirAsia.com to book airline tickets, even to book hotels and various attractive packages offered by AirAsia.com. E-business implemented by AirAsia is included in the B2C (Business-to-Consumer) application, which aims for consumers to directly contact the company without going through intermediaries. The focus of the problem in this research is how to implement e-business at PT AirAsia Indonesia, and what future steps/developments are proposed by the AirAsia company so that the e-business function can continue to grow and make the AirAsia company more competitive. This study aims to determine the e-business implemented by PT AirAsia Indonesia and alternative e-business development to increase competitive advantage. The method used to write this article is library research. To increase the competitive advantage AirAsia uses a CRM system that is useful for knowing the needs and behavior of changes by consumers.